Strategies for Effective Library and Information Centre Management - Dinesh, K. S.; Nikam, Khaiser (Journal of Information and Knowledge, 2007)
This paper on 'strategies for effective library and information centre management' is a survey of the librarians of engineering colleges in Karnataka. It reports the results of the opinions of the librarians regarding the strategies for location of libraries, factors influencing their use, effective management of library and information centre, to meet the goals and objectives, to integrate and coordinate the diverse activities of libraries, to become a part of engineering college library network. The results of the study are reported using statistical techniques.